Closed reduction and intramedullary nails for acute completely displaced femoral diaphysis fracture in children aged 2-6 - Fei Qiao; Xinpeng Shang; Fei Jiang (Frontiers Media S.A., 2024)
BackgroundThe management of femoral fractures in children aged two to six years is still controversial. The purpose of this study was to assess the results of closed reduction and elastic stable intramedullary nail (ESIN) fixation in completely displaced fractures of the femoral diaphysis in children in this age group.MethodsA retrospective review of all children with acute completely displaced fractures of the femoral diaphysis in children aged 2-6 years treated from 2013 to 2020 was performed. A total of 34 patients were treated who met the inclusion criteria: Group 1: 21 fractures (transverse and short oblique); Group 2: 13 fractures (long oblique and spiral) that underwent closed reduction and elastic stable intramedullary nail (ESIN) fixation. No differences existed between the 2 groups with respect to age, extremity, sex, time to treatment, mechanism of injury, or fracture displacement. Demographic characteristics and radiographs were reviewed, and the following parameters were documented: surgery time, time to union, return to activities, range of motion of knee joints, and complications. Major complications were defined as those with presumptive long-term side effects or those requiring a reoperation. No major complications were observed in the two groups. All included fractures were treated by a single senior paediatric surgeon. The mean follow-up period was 28.4 months (range 24-45 months). The level of significance was set at p < 0.05.ResultsThirty-four children with acute completely displaced fractures of the femoral diaphysis were included: Group 1: 21 fractures; Group 2: 13 fractures. The patients included 15 girls (44.1%) and 19 boys (55.9%), with an average age of 4.4 years (range 2.8 to 6.5 years). The mean follow-up period was 28.4 months (range 24.2-45.0 months). The demographic characteristics did not differ between the two groups of patients. Overall, successful closed reduction and elastic stable intramedullary nail (ESIN) fixation could be achieved in all 34 patients. The mean surgical time was 40.4 and 43.0 min in Group 1 and Group 2, respectively (p = 0.857). Fluoroscopy time was not significantly different between the two groups (37.0 vs. 36.1 s, respectively; p = 0.247). Cosmetic results were described as good and satisfactory by all patients. There were no refractures and no incidences of nonunion or growth arrest in the proximal epiphysis. Only two patients suffered from a superficial infection, which was resolved after the pins were shortened and oral antibiotics were administered.ConclusionClosed reduction and elastic stable intramedullary nail (ESIN) fixation can be successfully used to treat completely displaced fractures of the femoral diaphysis in children aged two to six years. This technique is efficient and minimally invasive, and the results are satisfactory.